A new technique in hydro thermal interconnected automatic generation control system by using minority charge carrier inspired algorithm. (June 2015) - Nanda, J.; Sreedhar, Madichetty; Dasgupta, Abhijit
Highlights: Use of electrical governor will provide better response than mechanical governor. Under various conditions, systems becomes stable with proper chosen of R values. Higher the R values weaker the response. MCI technique gives better results compared to ISE technique. Abstract: This article deals with Automatic Generation Control (AGC) of a multi area interconnected hydro thermal system in different modes using intelligent integral and proportional-integral controllers and provides the comparative analysis of electrical and mechanical governors. Appropriate Generation Rate Constraints (GRC) has been considered for the hydro and thermal generation plants. These cumulated thermal areas are considered with reheat turbines. Performances of reheat turbine mechanical governor and hydro turbine electrical governor with its dynamic responses have been investigated. Further, selection of suitable integral and proportional-integral controllers has been investigated with a Minority Charge carrier Inspired Algorithm (MCI). Cumulative system performance is examined considering with different load perturbation in both cumulative thermal areas. Further, system is investigated with different frequency bias values and results are explored.